THE DISTRIBUTION OF THE RATTAN INDUSTRY TO THE INCOME OF RATTAN CRAFTSMEN IN THE TRANGSAN VILLAGE GATAK DISTRICT SUKOHARJO DISTRICT IN 2020 - Fitria Nugraheni; MS Khabibur Rahman; Ary Wijayanti (Journal of Geography Science and Education, 2021)
This study aims to determine: 1) Distribution Map of the Rattan Industry in Trangsan Village, Gatak District, Sukoharjo Regency. (2) Region of Origin of Rattan Raw Materials in Trangsan Village, Gatak District, Sukoharjo Regency. (3) Socio-Economic Characteristics of Rattan Industry Craftsmen in Trangsan Village, Gatak District, Sukoharjo Regency. This research uses descriptive qualitative research methodology is a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. This study describes the Distribution Map of the Rattan Industry in Trangsan Village, Gatak District, Sukoharjo Regency, the Area of Origin of Rattan Raw Materials in Trangsan Village, Gatak District, Sukoharjo Regency, and the socio-economic characteristics of rattan industry craftsmen in Trangsan Village, Gatak District, Sukoharjo Regency. The data collection technique used is through direct field observation, interviews, questionnaires and documentation Based on the research that has been done, the results of this study are: (1) The results of the distribution of the rattan industry are 101 industries. (2) Regions of origin of rattan raw materials from Sulawesi and Kalimantan. (3) The socio-economic characteristics of rattan craftsmen whose industrial owners are aged 15-64 are 22 people aged> 65, there are 2 people, the highest education level is Bachelor degree, the income level is around 3,000,000 to over 9,000,000. Meanwhile, there are 48 people in the workforce aged 15-64, the highest level of education is SMA, the level of income per week is around 300,000 to 900,000.